2002
DOI: 10.1074/jbc.m207205200
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase-dependent Activation of Latent Transforming Growth Factor-β Controls the Conversion of Osteoblasts into Osteocytes by Blocking Osteoblast Apoptosis

Abstract: Upon termination of bone matrix synthesis, osteoblasts either undergo apoptosis or differentiate into osteocytes or bone lining cells. In this study, we investigated the role of matrix metalloproteinases (MMPs) and growth factors in the differentiation of osteoblasts into osteocytes and in osteoblast apoptosis. The mouse osteoblast cell line MC3T3-E1 and primary mouse calvarial osteoblasts were either grown on two-dimensional (2-D) collagen-coated surfaces, where they morphologically resemble flattened, cuboid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
168
0
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(175 citation statements)
references
References 58 publications
4
168
0
3
Order By: Relevance
“…Because TGF-␤ expression was upregulated after UUO to similar extents in Bsg ϩ/ϩ and Bsg Ϫ/Ϫ mice up to day 7, it is conceivable that the responsiveness to TGF-␤ is linked to the difference in renal fibrosis in Bsg ϩ/ϩ and Bsg Ϫ/Ϫ mice. In this context, it is noteworthy that both MMP-2 and MMP-9 are an activator of TGF-␤, 4,5 and that Bsg is a strong inducer of MMP family. Thus, there may be a molecular circuit between Bsg, MMPs, and TGF-␤ ( Figure 7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because TGF-␤ expression was upregulated after UUO to similar extents in Bsg ϩ/ϩ and Bsg Ϫ/Ϫ mice up to day 7, it is conceivable that the responsiveness to TGF-␤ is linked to the difference in renal fibrosis in Bsg ϩ/ϩ and Bsg Ϫ/Ϫ mice. In this context, it is noteworthy that both MMP-2 and MMP-9 are an activator of TGF-␤, 4,5 and that Bsg is a strong inducer of MMP family. Thus, there may be a molecular circuit between Bsg, MMPs, and TGF-␤ ( Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Conversely, some MMPs, such as MMP-2, MMP-9, and MT1-MMP, activate latent TGF-␤. 5,6 Therefore, ECM synthesis and degradation are intricately regulated by TGF-␤, MMPs, and others. In this context, it should also be noted that hyaluronan plays a crucial role in the TGF-␤-driven differentiation of fibroblasts into myofibroblasts.…”
mentioning
confidence: 99%
“…Other studies have shown that osteoblast survival is actually regulated by MT1-MMP through activation of transforming growth factor-β (TGFβ) [52]. Interestingly, TGFβ has also been implicated in the process of differentiation of hypertrophic chondrocyte through the upregulation of parathyroid-hormone-related protein (PTHrP) [53].…”
Section: Mt1-mmp Is Essential For Secondary Ossification and Chondrocmentioning
confidence: 99%
“…Later in development and subsequent to the delay in secondary-site ossification, proliferation of chondrocytes in the growth plate at the primary site is impaired. The progressive osteopenia observed in these mice results from a decrease in bone deposition, as well as an increase in bone resorption, with a high number of osteoclasts at the chondro-osseous junction.Other studies have shown that osteoblast survival is actually regulated by MT1-MMP through activation of transforming growth factor-β (TGFβ) [52]. Interestingly, TGFβ has also been implicated in the process of differentiation of hypertrophic chondrocyte through the upregulation of parathyroid-hormone-related protein (PTHrP) [53].…”
mentioning
confidence: 99%
“…10,15 The activation of TGF-b by the matricellular protein trombospondin-1, 16 as well as by the integrin a v b 6 17,18 seem to proceed via similar mechanisms. In addition, a number of proteases including plasmin, 19,20 matrix metalloproteinases MMP-3, -9, and MT1-MMP, 21,22 as well as exocytosed cathepsin B 23 have been identified as activators of latent TGF-b, at least in vitro.…”
Section: Introductionmentioning
confidence: 99%